Psikoedukasi sebagai upaya meningkatkan pengetahuan terkait feeling overwhelmed pada anggota kepolisian - Dwi Marva Kalisa; Giga Tabrilianti; Lukmanul Hakim (Penamas: Journal of Community Service, 2026)
Police officers face high occupational stress that may lead to feeling overwhelmed, a condition that occurs when job demands exceed an individual’s capacity to manage pressure. If unaddressed, it may develop into prolonged stress or burnout. This community outreach program aimed to improve police officers’ understanding of feeling overwhelmed through psychoeducation. A participatory approach combined a brief presentation and interactive discussion, with pretest and posttest assessments as evaluation tools. The program involved 10 officers from the Community Development Unit of the East Lombok Police Department selected through an initial assessment. Pretest results showed that 80% of participants did not understand the concept, while 20% had limited understanding. After the intervention, 80% achieved a good level of understanding, whereas 20% remained in the low category. The mean score increased from 2.7 to 13, and the average percentage rose by 63 points, from 17% to 80%. Participants also identified adaptive coping strategies. These findings indicate that psychoeducation can strengthen mental health literacy and support adaptive stress management among police officers.